The effect of educational intervention based on the health belief model on the domestic violence coping skills in women referring to comprehensive rural health service centers - Tayebeh Rakhshani; Sedigheh Poornavab; Seyyed Mansour Kashfi; Amirhossein Kamyab; Ali Khani Jeihooni (BMC Women's Health)
Abstract Background Domestic violence, in addition to the destructive effects it brings to the mother of the family, also has a strong impact on the children. According to the evidence obtained, coping strategies have been successful in tackling this issue. The purpose of this study was to investigate the effect of education on coping skills with domestic violence based on the health belief model (HBM) in women referring to comprehensive rural health service centers in Marvdasht City, Iran. Methods This semi-experimental study was conducted on 120 women affected by domestic violence who were referred to rural health centers in Marvdasht City in 2022. The multi-stage cluster sampling method was used for assigning people to two experimental and control groups (60 people in each group). The data collection tool was a questionnaire based on the HBM and a coping strategies questionnaire that was completed before and two months after the intervention by both groups. After entering SPSS 24, the data were analyzed by paired t, independent t, and chi-square statistical tests. Results Before the intervention between the two groups in terms of the constructs of awareness (P = 0.45), attitude (P = 0.23), behavior (P = 0.67), perceived sensitivity (P = 0.10), perceived severity (P = 0.84), perceived barriers (P = 0.31), perceived benefits (P = 0.21), perceived self-efficacy (P = 0.10), and cues to action (P = 0.19), no significant difference was observed, while after the intervention, a significant difference was observed between the two groups in terms of the structures expressed (P < 0.05). Likewise, before the intervention between the two experimental and control groups in terms of the ability to receive and send messages (P = 0.73), emotional control (P = 0.22), listening skills (P = 0.65), insight into the communication process (P = 0.15), communication combined with assertiveness (P = 0.98), and coping skills (P = 0.21), no significant difference was observed, while after the educational intervention, there was a significant difference between the two groups in terms of skill components (P = 0.001). Conclusion In the current study, education based on the HBM with a focus on coping skills led to the improvement of the skills of women who have experienced violence, their attitude and awareness, perceived sensitivity and perceived severity, and finally the benefits and barriers they receive from using coping skills.